2010
DOI: 10.1038/embor.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin nucleoporin phenylalanine–glycine repeat films and their interaction with nuclear transport receptors

Abstract: Ultrathin nucleoporin phenylalanine–glycine repeat films and their interaction with nuclear transport receptorsTo gain insight into the mechanisms behind transport of molecules across the nuclear pore complex, Richter and co-workers have developed ultrathin films of nucleoporin FG repeat domains and quantify how these films bind dedicated shuttle molecules—the so-called nuclear transport receptors (NTRs). They find that NTRs can efficiently permeate the films, but do not affect their global morphology, which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
163
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(204 citation statements)
references
References 23 publications
38
163
3
Order By: Relevance
“…This is supported by our observation that yeast GLFG domains can be compacted into the NPC or extended. Eisele et al (Eisele et al, 2010) showed, using atomic force microscopy, that dense FG domain films (with a similar density to the channel) did not collapse in the presence of importin b, but less densely packed ones could (Lim et al, 2007). This is consistent with the suggestion that some GLFG domains are densely packed in the channel and hence might not undergo reversible collapse (Eisele et al, 2010), but others can exist in extended, but reversibly collapsible conformations (Lim et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…This is supported by our observation that yeast GLFG domains can be compacted into the NPC or extended. Eisele et al (Eisele et al, 2010) showed, using atomic force microscopy, that dense FG domain films (with a similar density to the channel) did not collapse in the presence of importin b, but less densely packed ones could (Lim et al, 2007). This is consistent with the suggestion that some GLFG domains are densely packed in the channel and hence might not undergo reversible collapse (Eisele et al, 2010), but others can exist in extended, but reversibly collapsible conformations (Lim et al, 2007).…”
Section: Discussionsupporting
confidence: 74%
“…43,44 Similarly, FG-domains were used to coat supported lipid bilayers and to produce a densely attached ultrathin FG-domain film, to which the NTR could also bind. 67 The evidence from these studies supports the selective phase/hydrogel proposal. The cohesive FGNups include Nup42, Nup49, Nup57, Nup100, Nup116, and Nup145N.…”
Section: Distinct Transport Routes and Proposed Transport Modelssupporting
confidence: 71%
“…The bulk-like hydrogel meshwork model (5), for instance, places a greater importance on the hydrophobic interactions between neighbor FG-Nups, as they are able to form a sieve-like meshwork in vitro (10). Transport could then occur through binding of transport receptors to FG-repeats, causing a local gel-to-liquid transition and allowing the receptor to catalyze its own diffusion (28). Our data do not exclude that these interactions play a role in transport; however, they suggest that the most kinetically relevant events in the intact NPC have the characteristics of directed transport, not of unbiased diffusion.…”
Section: Resultsmentioning
confidence: 99%